Isolation and identification of cancer stem cells from PC3 human prostate carcinoma cell line - Zhou, Yaojun (Int J Clin Exp Pathol, 2017)
Objective: Morphological differences of PC3 clones were dynamically observed, and the expression of CD44 in different clones was detected to compare the tumorigenic ability of different clone cells in nude mice and identify the clones containing prostate cancer stem cells. Materials and methods: Clone formation assay was used for observing and classifying PC3 clones and calculating the cloning efficiency and the proportion of each clone. CD44 expression in different clones was detected by immunofluorescence technique. In addition, different morphologies of clones were isolated to measure the ability of self-renewing, and inoculated into nude mice to observe the tumorigenic ability. Results: PC3 cells could form three morphologies of clones, namely holoclone, meroclone, and paraclone. The cloning efficiency was 10.23%±0.91%, and the proportion of the three clones was 11.7%, 50.0% and 38.3%, respectively. Immunofluorescence showed that the expression of CD44 in holoclone was significantly stronger than meroclone and paraclone. Holoclone had self-renewing ability and strong tumorigenic ability in nude mice. Conclusion: There are differences in morphologies and differentiation of PC3 clones. Moreover, prostate cancer stem cells are abundant in holoclone.